Diagnostic Value and Prognostic Significance of Pleural C-Reactive Protein in Lung Cancer Patients with Malignant Pleural Effusions - Park, Do-Sim; Kim, Dong; Hwang, Ki-Eun; Hwang, Yu-Ri; Park, Chul; Seol, Chang-Hwan; Cho, Kyung-Hwa; Kim, Byoung-Ryun; Park, Seong-Hoon; Jeong, Eun-Taik; Kim, Hak-Ryul (Yonsei medical journal, 2013)
C-reactive protein (CRP) has been implicated in various inflammatory and advanced malignant states. Increased serum CRP (s-CRP) levels have been shown to be associated with independent prognostic factors for survival in patients with advanced lung cancer. However, only few studies have focused on the role of CRP in pleural effusions. This study aimed to evaluate the diagnostic and prognostic value of pleural CRP (p-CRP) in lung cancer patients with malignant pleural effusion (MPE). Pleural effusion (PE) samples were collected from patients with MPE (68 lung cancers; 12 extrathoracic tumors), and from 68 patients with various benign conditions (31 with pneumonia; 37 with tuberculosis). Concentrations of p- and s-CRP were measured by enzyme-linked immunosorbent assay. CRP level in pleural fluid and its association with survival were examined. p-CRP levels correlated with s-CRP levels (r=0.82, p<0.0001). For the differential diagnosis of MPE and benign PE, the area under the receiver operating characteristic curve was greater for p-CRP (0.86) than for s-CRP (0.77). High p-CRP expression significantly correlated with shorter overall survival (p=0.006). P-CRP was independent prognostic factor significantly associated with overall survival on multivariated analysis (p=0.0001). The relative risk of death for lung cancer patients with high p-CRP levels was 3.909 (95% confidence interval, 2.000-7.639). P-CRP is superior to s-CRP in determining pleural fluid etiology. Quantitative measurement of p-CRP might be a useful complementary diagnostic and prognostic test for lung cancer patients with MPE.